Predictors of PTSD Symptom Change Among Outpatients in the U.S. Department of Veterans Affairs Health Care System. Issue 1 (19th January 2017) - Sripada, Rebecca K.; Pfeiffer, Paul N.; Rampton, Jessica; Ganoczy, Dara; Rauch, Sheila A. M.; Polusny, Melissa A.; Bohnert, Kipling M.
Abstract : Although the U.S. Department of Veterans Affairs (VA) has prioritized care for posttraumatic stress disorder (PTSD), many patients with PTSD remain symptomatic. Patterns of PTSD symptom change are not well understood. Thus, the current study was designed to categorize and investigate potential predictors of symptom trajectories in patients with PTSD. The sample comprised 2, 237 VA patients who were diagnosed with PTSD in 2013 and completed at least 4 PTSD Checklist (PCL) assessments over 12 weeks. Latent trajectory analysis was used to identify latent classes of patients based on PCL scores. Based on model fit indices, 3 trajectories were identified. Compared to patients in the mild‐improving trajectory (21.9%), those in the severe‐stable trajectory (34.3%) were more likely to be male, relative risk ratio (RRR) = 1.48, 95% CI [1.08, 2.02]; non‐White, RRR = 1.77, 95% CI [1.33, 2.35]; Hispanic, RRR = 2.07, 95% CI [1.40, 3.04]; and have comorbid depression, RRR = 1.58, 95% CI [1.25, 1.99]. Compared to patients in the moderate‐improving trajectory (43.8%), those in the severe‐stable trajectory were more likely to have sleep disorders, RRR = 1.25, 95% CI [1.01, 1.55]. Our findings suggest that male veterans, minority veterans, and veterans with certain comorbid conditions may be less likely to achieve improved PTSD symptoms. Targeted efforts are needed to improve outcomes for PTSD patients on nonremitting trajectories and to improve the consistency of PTSD assessment across the VA health care system.